2009
DOI: 10.1158/0008-5472.can-09-2348
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Alters Cell Growth in Nonmalignant Colonocytes and Reduces the Formation of Preneoplastic Lesions in the Colon

Abstract: Numerous clinical and animal studies show that hormone replacement therapy reduces the risk of colon tumor formation. However, the majority of experiments have shown that estradiol (E 2 ) does not inhibit the growth of malignantly transformed colon epithelia. As such, the presented studies focused on evaluating the effects of E 2 in noncancerous colonocytes. E 2 treatments (0-10 nmol/L) reduced cell growth and increased apoptotic activity in young adult mouse colonocytes (YAMC), a nonmalignant cell line, in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 35 publications
5
58
1
Order By: Relevance
“…As early as a few hours following carcinogen exposure at the point of initial DNA damage, E 2 significantly induces apoptosis in the colonic epithelium of rats when compared with control mice (Armstrong et al 2011). In addition, we have demonstrated that E 2 suppresses the formation of premalignant lesions in the colon, which is again associated with an upregulation of apoptosis in colonic epithelia (Weige et al 2009). …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As early as a few hours following carcinogen exposure at the point of initial DNA damage, E 2 significantly induces apoptosis in the colonic epithelium of rats when compared with control mice (Armstrong et al 2011). In addition, we have demonstrated that E 2 suppresses the formation of premalignant lesions in the colon, which is again associated with an upregulation of apoptosis in colonic epithelia (Weige et al 2009). …”
Section: Discussionmentioning
confidence: 70%
“…Previous studies carried out in our laboratory and others have indicated that ERb, the primary ER within the colon, is the form of the receptor through which E 2 exerts its protective effects (Guo et al 2004, Weige et al 2009. Other groups have shown that ERbKO mice are more susceptible to inflammation-associated colon cancer than the WT mice (Saleiro et al 2012).…”
Section: Discussionmentioning
confidence: 88%
“…In experimental cell line and animal studies, protective effects of female sex hormones about colorectal carcinogenesis were found to be mediated by ESR2 (24)(25)(26)(27)(28)(29). Therefore, it is biologically plausible that exogenous hormones interact with ESR2 and downregulate the growth of neoplastic cells in the colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The YAMC cell line was initially generated from the Immorto mouse (Whitehead et al, 1993) and has been previously used in our studies (Kolar et al, 2007;Weige et al, 2009;Turk et al, 2011). Cells were maintained in RPMI 1640 medium with 5% fetal bovine serum, 5 units/ml mouse interferon-g (IF005) (EMD Millipore, Billerica, MA), 1% ITS "2" minus (insulin, transferrin, selenium) (41-400-045; Life Technologies, Grand Island, NY) at 33°C (permissive conditions).…”
Section: Methodsmentioning
confidence: 99%